Evidence for genetic heterogeneity in inflammatory bowel disease (IBD); HLA genes in the predisposition to suffer from ulcerative colitis (UC) and Crohn's disease (CD) - BOUMA, G (Blackwell Science Inc, 1997)
Family and epidemiological studies support a genetic susceptibility to UC and CD. Conflicting reports regarding associations between UC and HLA-DR2 and between CD and various HLA alleles have been published. The aim of this study was to determine whether molecularly defined HLA-DR genes are associated with these diseases in a Dutch group of patients. Fifty-nine unrelated Dutch UC patients and 89 CD patients were typed using DNA-based methods. A total of 2400 healthy local blood donors served as controls. The phenotype frequency of the HLA-DRB1*15 allele was increased in UC patients compared with controls (42% versus 26% in controls; P= 0.006; odds ratio (OR) = 2.1), and was predominantly found in female patients (53% versus 24%; P= 0.001; OR = 3.5). The DRB1*15 allele was increased in UC patients having a positive family history (P= 0.01; OR = 5.8). Among the 16 patients who showed an increase in extent of disease during follow up, 10 were DRB1*15(+) (P= 0.002; OR = 4.8). The frequency of the DRB1*13 allele was decreased in patients with UC (15% versus 28% in controls; P= 0.04; OR = 0.5). In CD, no association was observed between disease or particular clinical subgroups and any allele tested. The present study provides additional evidence for the genetic association between UC and HLA-DRB1*15, and supports recent findings that the susceptibility gene(s) for CD is not located in the HLA class II region.